THE EFFECT OF THE USE OF VIDEO AS A MEDIUM OF LEARNING ENGLISH TO IMPROVE STUDENTS' SKILLS IN WRITING PROCEDURE TEXTS - Helmi Helmi (Universitas Lambung Mangkurat, 2019)
The purpose of this study is to obtain evidence that there is an influence on the use of video on students' skills in writing procedure texts. This research was conducted in July 2019 in class IX of SMP Negeri 27 Banjarmasin. The method used is a quantitative method with a quasi-experiment design. The sampling technique used in this study is a purposive sampling method in which the researcher has had special consideration in choosing a research sample based on data provided by an English subject teacher at the school. The instrument used in this study is a test sheet that has been tested for validity and reliability. The two classes used as subjects in this study are called the experimental class and the control class which for the experimental class is taught through video and the control class is taught using audio media only by using speakers without image or visual display. The class that is an experimental group is a class that has a lower value than the pre-test results, so the researcher wants to prove whether video media can increase that value. The data obtained from the two experimental and control groups were tested for normality and homogeneity first and then the independent sample t-test was conducted. The results show that the significance value (2-tailed) from the analysis of independent sample t-test shows that the value is smaller than 0.05 where the value obtained is 0.00 so based on statistical decision in making provisions if the value is lower than 0.05 then there is a significant difference between the post-test results of students taught by using video and audio media only through speaker facilities in the ninth grade at SMPN 27 Banjarmasin.